A rigid crosslinked polyvinyl chloride material and a method for its production
Patent Information
- Application Number
- CN202211124167.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-13
- Publication Date
- 2026-09-25
- Estimated Expiration
- 2042-09-13
AI Technical Summary
现有工艺中,交联型聚氯乙烯板材通常通过模压法完成,不便于工业上的连续生产
[0023]1)本发明的硬质交联聚氯乙烯材料的制备方法采用挤出方法,工艺简单、周期短、所需成本较低,利于工业连续性生产;
Smart Images

Figure CN117736521B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of chemical crosslinking modification and reinforcement technology of polyvinyl chloride sheets, specifically relating to a rigid crosslinked polyvinyl chloride material and its preparation method. Background Technology
[0002] Polyvinyl chloride (PVC) is one of the most widely produced thermoplastic polymers. It is inexpensive and offers excellent value, but its structural instability results in relatively poor mechanical properties and heat resistance, which limits its applications. Common modification methods to improve the mechanical properties, heat resistance, and solvent resistance of PVC products include blending, filling, grafting, crosslinking, and copolymerization.
[0003] Crosslinking modification is one of the important methods to improve the heat resistance, flexural strength, modulus, tensile strength, and abrasion resistance of polyvinyl chloride (PVC). Crosslinking methods are mainly divided into radiation crosslinking and chemical crosslinking. Radiation crosslinking appeared earlier, but its mechanism is complex, and many influencing factors are difficult to control. Chemical crosslinking includes silane crosslinking, peroxide crosslinking, polythiol compound crosslinking, and polyamine compound crosslinking. In existing processes, crosslinked PVC sheets are usually produced by molding, which is not convenient for continuous industrial production. Summary of the Invention
[0004] In view of the above analysis, the present invention aims to provide a rigid cross-linked polyvinyl chloride material and its preparation method, which can solve one of the following technical problems: (1) Existing cross-linked polyvinyl chloride sheets are usually made by molding, which is not convenient for continuous industrial production; (2) Existing cross-linked polyvinyl chloride sheets have poor mechanical properties.
[0005] The objective of this invention is mainly achieved through the following technical solutions:
[0006] On one hand, the present invention provides a method for preparing a rigid cross-linked polyvinyl chloride material, comprising the following steps:
[0007] S1. The lubricant and the modified crosslinking agent are mixed to obtain the first mixture;
[0008] S2. After mixing the first mixture, polyvinyl chloride resin, processing aid, stabilizer, acid-binding agent and filler evenly, a dry mixture is obtained.
[0009] S3. Add the dry mixture to the conical twin-screw extrusion platform and extrude it from the die head to obtain a rigid cross-linked polyvinyl chloride preform;
[0010] S4. The rigid cross-linked polyvinyl chloride preform is cooled and shaped to obtain a rigid cross-linked polyvinyl chloride material.
[0011] Furthermore, the preparation method of the modified crosslinking agent includes:
[0012] Step 1: Dissolve melamine and formaldehyde in water to form an aqueous solution and reflux to obtain MF prepolymer;
[0013] Step 2: The crosslinking agent, which is dispersed in water under the action of the dispersant, is added to the MF prepolymer to carry out a polycondensation reaction; after the reaction is completed, the mixture is cooled, filtered, washed, and vacuum dried to obtain the modified crosslinking agent.
[0014] Furthermore, in S1, the lubricant is one or more of oxidized polyethylene wax, polyethylene wax, paraffin wax, and pentaerythritol stearate.
[0015] Furthermore, in S1, the mass ratio of lubricant to modified crosslinking agent is 0.6–1.0:4–20.
[0016] Furthermore, in S2, the processing aid is a combination of one or more acrylate copolymers.
[0017] Furthermore, in S2, the stabilizer is a calcium-zinc composite stabilizer.
[0018] Furthermore, in S2, the acid-binding agent is one or more of magnesium oxide or zinc oxide.
[0019] Furthermore, in S2, the mass ratio of modified crosslinking agent, polyvinyl chloride resin, processing aid, stabilizer, acid-binding agent and filler is 4-20:100:3-15:5-8:4-20:100-20.
[0020] Furthermore, in step 2, the modified crosslinking agent obtained includes a shell layer and a core layer, wherein the shell layer is MF resin and the core layer is a crosslinking agent.
[0021] The present invention also provides a rigid cross-linked polyvinyl chloride material, which is prepared by the above-described preparation method.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0023] 1) The preparation method of the rigid cross-linked polyvinyl chloride material of the present invention adopts the extrusion method, which is simple, has a short cycle, and requires low cost, and is conducive to continuous industrial production;
[0024] 2) In the preparation method of the rigid cross-linked polyvinyl chloride material of the present invention, the apparent density of the dry mixture is increased and the bridging phenomenon during the extrusion process is reduced by controlling the feeding sequence of different raw materials.
[0025] 3) In the preparation method of the rigid crosslinked polyvinyl chloride material of the present invention, a modified crosslinking agent comprising a shell layer and a core layer is used, wherein the shell layer is MF resin and the core layer is a crosslinking agent. During the extrusion process, the modified crosslinking agent destroys the MF resin shell layer through the shear force between the extruder screws and the friction with other materials, exposing the core layer crosslinking agent. This allows the effective components of the modified crosslinking agent to be released slowly and slows down the rate of crosslinking reaction between the crosslinking agent and polyvinyl chloride, thereby ensuring the smooth progress of the extrusion process.
[0026] 4) The rigid cross-linked polyvinyl chloride material prepared by the method of the present invention has good mechanical properties and heat resistance, which is beneficial to industrial production and wider application.
[0027] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the invention. The objects and other advantages of the invention may be realized and obtained by means of what is particularly pointed out in the written description and the accompanying drawings. Attached Figure Description
[0028] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.
[0029] Figure 1a This is a scanning electron microscope image of the morphology of the modified crosslinking agent of the present invention;
[0030] Figure 1b This is a transmission electron microscope image of the morphology of the modified crosslinking agent of the present invention;
[0031] Figure 2 EDS energy dispersive spectroscopy analysis data before and after extrusion in Example 3;
[0032] Figure 3 This is a physical image of the rigid cross-linked polyvinyl chloride material of the present invention. Detailed Implementation
[0033] Preferred embodiments of the present invention are described in detail below.
[0034] In existing processes, cross-linked PVC sheets are typically produced through compression molding, which is not convenient for continuous industrial production. Through long-term in-depth research, the applicant discovered that using a mercapto cross-linking agent to cross-link PVC results in an excessively rapid cross-linking reaction. Higher degrees of cross-linking in PVC lead to higher melt strength, making it difficult to directly extrude highly cross-linked PVC materials using an extrusion process.
[0035] This invention provides a method for preparing a rigid cross-linked polyvinyl chloride material, comprising the following steps:
[0036] S1. The lubricant and the modified crosslinking agent are mixed to obtain the first mixture;
[0037] S2. After mixing the first mixture, polyvinyl chloride resin, processing aid, stabilizer, acid-binding agent and filler evenly, a dry mixture is obtained.
[0038] S3. Add the dry mixture to the conical twin-screw extrusion platform and extrude it from the die head to obtain a rigid cross-linked polyvinyl chloride preform;
[0039] S4. The rigid cross-linked polyvinyl chloride preform is cooled and shaped by a sizing traction machine to obtain rigid cross-linked polyvinyl chloride material after cooling.
[0040] It should be noted that the preparation method of the above-mentioned modified crosslinking agent includes:
[0041] Step 1: Dissolve melamine and formaldehyde in water to form an aqueous solution and reflux to obtain MF prepolymer;
[0042] Step 2: The crosslinking agent, which is dispersed in water under the action of the dispersant, is added to the MF prepolymer to carry out a polycondensation reaction; after the reaction is completed, the mixture is cooled, filtered, washed, and vacuum dried to obtain the modified crosslinking agent.
[0043] Specifically, in step 1 above, considering that melamine contains three amino groups, in order to ensure that the reaction between melamine and formaldehyde is complete under ideal conditions, the molar ratio of melamine to formaldehyde is controlled to be 1:3.
[0044] Specifically, in step 2 above, the crosslinking agent is a multi-thiol crosslinking agent, including one or more of 2-n-butylamino-4,6-dimercaptotriazine, heterocyclic dimercapto quaternary ammonium salt, or triazole dimercaptoammonium salt.
[0045] Specifically, in step 2 above, the dispersant includes one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and sodium hexametaphosphate.
[0046] Specifically, in step 2 above, considering that excessive dispersant would complicate the subsequent removal process and that the modified crosslinking agent might contain impurities, the mass ratio of dispersant to crosslinking agent is controlled to be 1:25–35.
[0047] Specifically, in step 2 above, the reaction conditions for the polycondensation reaction are to stir the mixture with a pH of 4 to 6 at 70 to 90°C for 2 to 3 hours.
[0048] It should be noted that the modified crosslinking agent obtained in step 2 above includes a shell layer and a core layer. The shell layer is MF resin, and the core layer is a crosslinking agent.
[0049] Specifically, the modified crosslinking agent obtained in step 2 above is spherical or near-spherical particles with a particle size of 0.15 to 0.3 micrometers.
[0050] Specifically, in S1 above, the lubricant is one or more of oxidized polyethylene wax, polyethylene wax, paraffin wax, and pentaerythritol stearate.
[0051] Specifically, in S1 above, considering that adding too much lubricant will lead to prolonged or shortened plasticizing time and reduced mechanical properties, while adding too little will result in adhesion and other phenomena, failing to achieve the lubrication effect, the mass ratio of lubricant to modified crosslinking agent is controlled at 0.6–1.0:4–20.
[0052] Specifically, in S2 above, the processing aid is a combination of one or more acrylate copolymers (ACRs). The function of the processing aid is to promote plasticization and effectively reduce the difficulty of formula adjustment. The stabilizer is a calcium-zinc composite stabilizer. The function of the stabilizer is to prevent degradation of PVC due to high temperature during processing. The acid binder is one or more of magnesium oxide or zinc oxide. The function of the acid binder is to absorb and neutralize the hydrogen chloride released during crosslinking. The filler includes one or more of light calcium powder, titanium dioxide, impact modifier, and additives (the additives can be a combination of one or more acrylate copolymers (ACRs)). These fillers improve the appearance and performance of the material to a certain extent.
[0053] Specifically, in S2 above, considering the processability of the material and subsequent industrial applications, the mass ratio of modified crosslinking agent, polyvinyl chloride resin, processing aid, stabilizer, acid binder and filler is controlled to be 4-20:100:3-15:5-8:4-20:100-20.
[0054] Specifically, in S2 above, material mixing can be carried out in a small high-speed mixer. Considering that excessively high temperature, excessively high speed, and excessively long time will lead to material degradation, while excessively low temperature, excessively low speed, and excessively short time will not achieve the premixing effect, the temperature of the mixed materials is controlled at 100-120℃, the speed at 800-1400 rpm, and the time at 10-40 min.
[0055] Specifically, in the above preparation method, the lubricant and modified crosslinking agent are pre-mixed and then blended with other raw materials in order to improve the apparent density of the dry mixture and reduce bridging during the extrusion process.
[0056] Specifically, in S2 above, the dry mix is a loose, free-flowing powdery mixture. The apparent density of the dry mix is 0.4–0.7 g / cm³. 3 .
[0057] Specifically, in S3 above, the conical twin-screw extrusion platform comprises four parts: zone one, zone two, zone three, and the die head. Zone one primarily evaporates and transports moisture from the dry mix, requiring no high temperature. Zones two and three mainly involve compression and melting, where shear force occurs most intensely; excessive temperature and frictional heat must be prevented to avoid premature release of the crosslinking agent and subsequent material degradation. A slightly higher die head temperature allows the slowly released active ingredients of the modified crosslinking agent to be fully utilized. Therefore, the temperature of each zone should be controlled according to the following relationship: zone one < zone two ≤ zone three < die head. For example, zone one temperature is 160–175℃, zone two temperature is 170–180℃, zone three temperature is 170–185℃, and the die head temperature is 180–190℃.
[0058] Specifically, in S3 above, the modified crosslinking agent breaks down the MF resin in the shell layer by shearing force between the extruder screws and friction with other materials, exposing the core layer. This allows the effective components of the modified crosslinking agent to be released slowly, which slows down the crosslinking reaction between the crosslinking agent and polyvinyl chloride, thereby ensuring the smooth progress of the extrusion process.
[0059] Specifically, the present invention also provides a rigid cross-linked polyvinyl chloride material, which is prepared by the above-described preparation method.
[0060] Example 1
[0061] This embodiment provides a rigid crosslinked polyvinyl chloride material and its preparation method. The raw material composition is as follows: 100 parts by weight of polyvinyl chloride resin, 3 parts by weight of processing aid ZB-750, 5 parts by weight of calcium-zinc composite stabilizer, 10 parts by weight of acid-binding agent magnesium oxide, 10.5 parts by weight of modified crosslinking agent, 0.3 parts by weight of lubricant oxidized polyethylene wax, 0.3 parts by weight of lubricant polyethylene wax, 25 parts by weight of light calcium powder, 1 part by weight of titanium dioxide, and 1 part by weight of processing aid ZB-175.
[0062] The preparation method of the above-mentioned rigid cross-linked polyvinyl chloride material is as follows:
[0063] (1) First, the lubricant and the modified crosslinking agent are mixed to obtain a first mixture; then, the other components of the corresponding mass proportions are added to a high-speed mixer, the mixing temperature is 100℃, the mixing speed is 800 rpm / h, and the mixing time is 15 min. After uniform mixing, an apparent density of 0.52 g / cm³ is obtained. 3 Dry mix;
[0064] (2) The dry mixture is added to the conical twin-screw extrusion platform. The temperature of zone 1 is 160°C, the temperature of zone 2 is 170°C, the temperature of zone 3 is 175°C, and the temperature of the die head is 180°C. After extrusion from the die head, a rigid cross-linked polyvinyl chloride preform is obtained.
[0065] (3) The rigid cross-linked polyvinyl chloride preform is directly cooled and shaped by a sizing traction machine, and a rigid cross-linked polyvinyl chloride material with high toughness is prepared after cooling.
[0066] Specifically, the preparation method of the above-mentioned modified crosslinking agent includes:
[0067] Step 1: Melamine and formaldehyde are dissolved in water to form an aqueous solution and then refluxed to obtain MF prepolymer; the molar ratio of melamine to formaldehyde is 1:3.
[0068] Step 2: The crosslinking agent, dispersed in water under the action of a dispersant, is added to the MF prepolymer to carry out a polycondensation reaction; after the reaction is completed, the mixture is cooled, filtered, washed, and vacuum dried to obtain the modified crosslinking agent; the dispersant is sodium dodecyl sulfate. The mass ratio of dispersant to crosslinking agent is 1:32.
[0069] Example 2
[0070] This embodiment provides a rigid crosslinked polyvinyl chloride material and its preparation method. The raw material composition is as follows: 100 parts by weight of polyvinyl chloride resin, 4 parts by weight of processing aid ZB-750, 6 parts by weight of calcium-zinc composite stabilizer, 15 parts by weight of acid-binding agent zinc oxide, 15 parts by weight of modified crosslinking agent, 0.4 parts by weight of lubricant oxidized polyethylene wax, 0.3 parts by weight of lubricant paraffin wax, 30 parts by weight of light calcium powder, 5 parts by weight of titanium dioxide, and 2 parts by weight of processing aid ZB-175.
[0071] The preparation method of the above-mentioned rigid cross-linked polyvinyl chloride material is as follows:
[0072] (1) First, the lubricant and the modified crosslinking agent are mixed to obtain a first mixture; then, the corresponding mass proportions of the above components are added together to a high-speed mixer. The mixing temperature is 100℃, the mixing speed is 900 rpm / h, and the mixing time is 20 min. After uniform mixing, an apparent density of 0.50 g / cm³ is obtained. 3 Dry mix;
[0073] (2) The dry mixture is added to the conical twin-screw extrusion platform. The temperature of zone 1 is 165°C, the temperature of zone 2 is 175°C, the temperature of zone 3 is 175°C, and the temperature of the die head is 185°C. After extrusion from the die head, a rigid cross-linked polyvinyl chloride preform is obtained.
[0074] (3) Finally, the rigid cross-linked PVC preform is cooled and shaped directly by a shaping traction machine, and a rigid cross-linked PVC material with high toughness is prepared after cooling.
[0075] Specifically, the preparation method of the above-mentioned modified crosslinking agent includes:
[0076] Step 1: Dissolve melamine and formaldehyde in water to form an aqueous solution and reflux to obtain MF prepolymer; the molar ratio of melamine to formaldehyde is 1:3.
[0077] Step 2: The crosslinking agent, which is dispersed in water under the action of the dispersant, is added to the MF prepolymer to carry out a polycondensation reaction; after the reaction is completed, the mixture is cooled, filtered, washed, and vacuum dried to obtain the modified crosslinking agent; the dispersant is sodium dodecyl sulfate; the mass ratio of dispersant to crosslinking agent is 1:30.
[0078] Example 3
[0079] This embodiment provides a rigid crosslinked polyvinyl chloride material and its preparation method. The raw material composition is as follows: 100 parts by weight of polyvinyl chloride resin, 5 parts by weight of processing aid ZB-750, 8 parts by weight of calcium-zinc composite stabilizer, 20 parts by weight of acid-binding agent magnesium oxide, 20 parts by weight of modified crosslinking agent, 0.6 parts by weight of lubricant polyethylene wax, 0.4 parts by weight of lubricant paraffin wax, 30 parts by weight of light calcium powder, 5 parts by weight of titanium dioxide, and 5 parts by weight of processing aid ZB-175.
[0080] The preparation method of the above-mentioned rigid cross-linked polyvinyl chloride material is as follows:
[0081] (1) First, the lubricant and the modified crosslinking agent are mixed to obtain a first mixture; then, the corresponding mass proportions of the above components are added to a high-speed mixer, the mixing temperature is 100℃, the mixing speed is 850 rpm / h, and the mixing time is 15 min. After uniform mixing, an apparent density of 0.48 g / cm³ is obtained. 3 Dry mix;
[0082] (2) The dry mixture is added to the conical twin-screw extrusion platform. The temperature of zone 1 is 175°C, the temperature of zone 2 is 180°C, the temperature of zone 3 is 185°C, and the temperature of the die head is 190°C. After extrusion from the die head, a rigid cross-linked polyvinyl chloride preform is obtained.
[0083] (3) The rigid cross-linked polyvinyl chloride preform is directly cooled and shaped by a sizing traction machine, and a rigid cross-linked polyvinyl chloride material with high toughness is prepared after cooling.
[0084] Figure 1a This is a scanning electron microscope image of the morphology of the modified crosslinking agent of the present invention; Figure 1b This is a transmission electron microscope (TEM) image of the morphology of the modified crosslinking agent of the present invention. The image shows that the modified crosslinking agent has a spherical particle morphology with a particle size of approximately 0.2 micrometers. The crosslinking agent is successfully encapsulated within the spherical particles (through...). Figure 1b (It can be obtained within the inner red box).
[0085] Figure 2The data are EDS energy dispersive spectroscopy analysis data before and after extrusion in Example 3. As can be seen from the figure, the increases in S and Ti before and after extrusion are relatively large, indicating that the shear force and friction with other materials during the extrusion process can successfully release the crosslinking agent inside the modified crosslinking agent.
[0086] Figure 3 This is a physical image of the rigid cross-linked polyvinyl chloride material of the present invention.
[0087] The applicant conducted extensive research on various options during the research process, and some of the less effective options are listed below as comparative examples:
[0088] Comparative Example 1
[0089] This comparative example provides a rigid crosslinked polyvinyl chloride material and its preparation method. The rigid polyvinyl chloride material is composed of: 100 parts by weight of polyvinyl chloride resin, 4 parts by weight of processing aid ZB-750, 7 parts by weight of calcium-zinc composite stabilizer, 0.6 parts by weight of lubricant oxidized polyethylene wax, 0.3 parts by weight of lubricant polyethylene wax, 20 parts by weight of light calcium powder, 3 parts by weight of titanium dioxide, and 2 parts by weight of processing aid ZB-175.
[0090] The preparation method of the above-mentioned rigid cross-linked polyvinyl chloride material is as follows:
[0091] (1) First, add the components of the corresponding mass fractions to a high-speed mixer. The mixing temperature is 45℃, the mixing speed is 800rpm / h, and the mixing time is 15min. After uniform mixing, a dry mixture is obtained.
[0092] (2) The dry mixture is added to the conical twin-screw extrusion platform. The temperature of zone 1 is 170°C, the temperature of zone 2 is 170°C, the temperature of zone 3 is 180°C, and the temperature of the die head is 185°C. After extrusion from the die head, rigid polyvinyl chloride preform is obtained.
[0093] (3) Finally, the rigid PVC preform extruded from the die head is directly cooled and shaped by a sizing traction machine, and then the rigid PVC material is prepared.
[0094] Comparative Example 2
[0095] This comparative example provides a rigid crosslinked polyvinyl chloride material and its preparation method. The rigid crosslinked polyvinyl chloride material is composed of: 100 parts by weight of polyvinyl chloride resin, 5 parts by weight of processing aid ZB-750, 6 parts by weight of calcium-zinc composite stabilizer, 16 parts by weight of acid-binding agent magnesium oxide, 1 part by weight of crosslinking agent, 0.7 parts by weight of lubricant oxidized polyethylene wax, 0.3 parts by weight of lubricant polyethylene wax, 25 parts by weight of light calcium powder, 3 parts by weight of titanium dioxide, and 2 parts by weight of processing aid ZB-175.
[0096] The preparation method of the above-mentioned rigid cross-linked polyvinyl chloride is as follows:
[0097] (1) First, add the components of the corresponding mass fractions to a high-speed mixer. The mixing temperature is 45℃, the mixing speed is 800rpm / h, and the mixing time is 15min. After uniform mixing, a dry mixture is obtained.
[0098] (2) The dry mixture is added to the conical twin-screw extrusion platform. The temperature of zone 1 is 170°C, the temperature of zone 2 is 175°C, the temperature of zone 3 is 180°C, and the temperature of the die head is 185°C. After extrusion from the die head, a rigid cross-linked polyvinyl chloride preform is obtained.
[0099] (3) Finally, the rigid cross-linked polyvinyl chloride preform is cooled and shaped directly by a shaping traction machine, and the rigid cross-linked polyvinyl chloride material is prepared after cooling.
[0100] Comparative Example 3
[0101] This comparative example provides a rigid cross-linked polyvinyl chloride material and its preparation method. The raw material composition is the same as that in Example 2. The difference in the preparation method is that all the mixtures are mixed together in (1).
[0102] (1) The components in the corresponding mass proportions mentioned above were added together to a high-speed mixer. The mixing temperature was 100℃, the mixing speed was 900 rpm / h, and the mixing time was 20 min. After uniform mixing, an apparent density of 0.45 g / cm³ was obtained. 3 Dry mix;
[0103] (2) The dry mixture is added to the conical twin-screw extrusion platform. The temperature of zone 1 is 160°C, the temperature of zone 2 is 165°C, the temperature of zone 3 is 170°C, and the temperature of the die head is 175°C. After extrusion from the die head, a rigid cross-linked polyvinyl chloride preform is obtained.
[0104] (3) The rigid cross-linked polyvinyl chloride preform is directly cooled and shaped by a sizing traction machine, and a rigid cross-linked polyvinyl chloride material with high toughness is prepared after cooling.
[0105] The performance data of the rigid cross-linked polyvinyl chloride (PVC) materials of the examples and comparative examples are shown in Table 1 below. As can be seen from the table, the rigid cross-linked PVC materials prepared by the present invention have a gel content of 31.3% or more, for example, 31.3% to 45.7%; a Vicat softening temperature of 85.2°C or more, for example, 85.2 to 87.1°C; an average Shore hardness of 80.8 or more, for example, 80.8 to 83.0; a flexural strength of 77 MPa or more, for example, 77.3 to 81.1 MPa; a flexural modulus of 4250 MPa or more, for example, 4250.4 to 4766.5 MPa; a tensile strength of 37.5 MPa or more, for example, 37.5 to 40.2 MPa; and a tensile modulus of 1950 MPa or more, for example, 1954.2 to 2176.8 MPa. It is evident that the rigid cross-linked PVC materials prepared by the method of the present invention exhibit high mechanical strength and excellent heat resistance.
[0106] Table 1. Performance data of rigid cross-linked polyvinyl chloride prepared in the examples and comparative examples.
[0107]
[0108] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a rigid cross-linked polyvinyl chloride material, characterized in that, Includes the following steps: S1. The lubricant and the modified crosslinking agent are mixed to obtain a first mixture; the modified crosslinking agent includes a shell layer and a core layer, the shell layer is MF resin, and the core layer is a crosslinking agent; S2. After uniformly mixing the first mixture, polyvinyl chloride resin, processing aid, stabilizer, acid-binding agent and filler, a dry mixture is obtained; the processing aid is a combination of one or more acrylate copolymers; S3. The dry mixture is added to a conical twin-screw extrusion platform and extruded from the die head to obtain a rigid cross-linked polyvinyl chloride preform; S4. The rigid cross-linked polyvinyl chloride preform is cooled and shaped to obtain a rigid cross-linked polyvinyl chloride material.
2. The preparation method according to claim 1, characterized in that, The preparation method of the modified crosslinking agent includes: Step 1: Dissolve melamine and formaldehyde in water to form an aqueous solution and reflux to obtain MF prepolymer; Step 2: The crosslinking agent, which is dispersed in water under the action of the dispersant, is added to the MF prepolymer to carry out a polycondensation reaction; after the reaction is completed, the mixture is cooled, filtered, washed, and vacuum dried to obtain the modified crosslinking agent.
3. The preparation method according to claim 1, characterized in that, In S1, the lubricant is one or more of oxidized polyethylene wax, polyethylene wax, paraffin wax, and pentaerythritol stearate.
4. The preparation method according to claim 1, characterized in that, In S1, the mass ratio of lubricant to modified crosslinking agent is 0.6~1.0:4~20.
5. The preparation method according to claim 1, characterized in that, In S2, the stabilizer is a calcium-zinc composite stabilizer.
6. The preparation method according to claim 1, characterized in that, In S2, the acid-binding agent is one or more of magnesium oxide or zinc oxide.
7. The preparation method according to claim 1, characterized in that, In S2, the mass ratio of modified crosslinking agent, polyvinyl chloride resin, processing aid, stabilizer, acid-binding agent and filler is 4~20:100:3~15:5~8:4~20:100~20.
8. A rigid cross-linked polyvinyl chloride material, prepared by the preparation method according to any one of claims 1-7.